Assessing hiking trails condition in two popular tourist destinations in the Icelandic highlands - Ólafsdóttir, Rannveig; Runnström, Micael C. (Journal of Outdoor Recreation and Tourism, 2013)
Nature-based tourism in the fragile Arctic environments is emerging as a major environmental concern, mainly due to extreme seasonality in these locations, the lack of suitable infrastructures and planning, and its interference with fragile ecosystems. In Iceland tourism has increased exponentially during the past decades, causing more environmental impacts on the country's natural recourses. Hiking is one of the most popular tourist activities in Iceland, especially in the interior highlands. This study had two goals: to map the current status of hiking trail conditions in two popular tourist destinations of the southern highlands, Pórsmörk and Fjallabak Nature Reserve (FNR); and to examine the relationship between trail condition assessment and local physical properties, such as elevation, gradient, soil type, and vegetation cover, in GIS. The current status of the hiking trails is much worse in the Pórsmörk area, where over 30% of the trail system is classified as being in bad and very bad condition, compared to 12% for the FNR. Of the analyzed physical properties only elevation has a clear relationship with hiking trail condition in both study sites and gradient in the Pórsmörk area. Importantly, severe conditions never apply to a whole trail, suggesting that trail conditions are a function of trampling magnitude and local physical properties. Hence, when maintaining hiking trails in vulnerable environments, such as the Icelandic highlands, a holistic understanding of the environmental impact of trampling is critical. Management implications When nature-based tourism enters very fragile environments, good monitoring techniques become even more important. Such is the case on hiking trails in the highlands of Iceland, where the study produced the following findings: Monitoring the conditions of hiking trails is vital for understanding the major causes of trail degradation in the Icelandic highlands. Implementing a visual field assessment with a condition scale based on simplified classification system, a whole ...